-48=6(a-1)

Simple and best practice solution for -48=6(a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -48=6(a-1) equation:


Simplifying
-48 = 6(a + -1)

Reorder the terms:
-48 = 6(-1 + a)
-48 = (-1 * 6 + a * 6)
-48 = (-6 + 6a)

Solving
-48 = -6 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-48 + -6a = -6 + 6a + -6a

Combine like terms: 6a + -6a = 0
-48 + -6a = -6 + 0
-48 + -6a = -6

Add '48' to each side of the equation.
-48 + 48 + -6a = -6 + 48

Combine like terms: -48 + 48 = 0
0 + -6a = -6 + 48
-6a = -6 + 48

Combine like terms: -6 + 48 = 42
-6a = 42

Divide each side by '-6'.
a = -7

Simplifying
a = -7

See similar equations:

| x+2x+x+25=165 | | 4+7x=34-x | | -57=-5x+8(3+4x) | | 5+8m=-1+5m | | 6x-5=4x-53 | | y=.666x-1 | | 6x-4x+7=0 | | 4x-2(x+3)=3x | | 63=-7(3n-3) | | X=-3.6X^2-8.8X+8.3 | | 6x-3(4+x)=0 | | 4x=-25 | | 47533.32=2*3.14*r^2+2*3.14*r*232 | | f/5+4=29 | | -2(9-3x)+2=-4 | | -73=6m-5(m-3) | | 7-3(2-x)+6=-2 | | 72*64-7/80+4*x=40*52*2 | | -6(x-3)-8=-8 | | 3265+28=oshawn | | 4=4a-8(a-2) | | -8+3(x-6)=1 | | -9(x+4)=18 | | 6(-3-x)+8=-16 | | 4(-x+4)+6=2 | | 20=6(2+x)+8 | | 743-28=x | | 4-3(2-2x)=4 | | x(x-2)(x+3)=0 | | 4(2-x)-7x=41 | | 1g+2=-6g+3+8g+4 | | (3x-5)(x^2-8x+7)=0 |

Equations solver categories